Sirens of the Western shore : the westernesque femme fatale, translation, and vernacular style in modern Japanese literature - Levy, Indra A. (Columbia University Press, 2006)
A study that introduces an archetype in modern Japanese literature, this work pinpoints the birth of the Westernesque femme fatale in the vernacularist movement of the late 1880s, tracks her development in naturalist fiction of the mid-1900s, and finds her catapulted to centre stage in the early 1910s.